RANCANGAN PLTS ATAP GEDUNG GEREJA METHODIST INDONESIA MANNA HELVETIA - Kenny Angel Manik; Wayan Gede Ariastina; Ida Ayu Dwi Giriantari (Jurnal SPEKTRUM, 2023)
Indonesia have potential sunshine over year, it makes indoensia has a large source of renewable energy. However, renewable energy usage is very low. One of the renewable energy is solar power plants (PLTS). Medan City is one of the highly populated cities and it makes Medan city very limited land to build PLTS, and the solution is to build rooftop PLTS. Therefore, this research discusses the planning of PLTS on the roof of the Manna Helvetai Indonesian Methodist Church Building. The design of this PLTS is simulated using the Helioscope simulator. Solar modules are installed as many as 35 pieces and have 1 inverter with a capacity of 20 kW and produce potential energy of 15.8 kWp. Based on the results of the rooftop solar power plant design and the results of the calculation of electrical energy production, it can be analyzed that the economic development of rooftop solar power plants is considered feasible because it meets the criteria of Net Present Value (NPV) greater than zero, namely Rp 44,638,904 and Benefit-Cost Ratio (B-CR) greater than one, namely 1.19 and Discounted Payback Period (DPP) which is reached at the life of the solar power plant.